Clinical Pharmacology 2008: Practical Information for Physicians, Nurses and Pharmacists. Issue 4 (July 2008) - Albertson, Timothy E; Grubbs, John
This annual Clinical Pharmacology update was sponsored by the UC Davis Health System, Office of Continuing Education and by the Department of Pharmacy and was located in the beautiful Napa Valley (CA, USA). The diverse and talented faculty of physicians and clinical pharmacists reviewed new medications and advances in state-of-the-art therapeutics, which are important in the treatment of disease.